Reinforcement and Restoration Studies of the Edremit Ataturk House - Bagbanci, B. M. (Engineering, Technology & Applied Science Research, 2020)
Edremit Ataturk House has been restored under international restoration principles. Due to its importance, a systematic study was carried out to prevent the building from suffering damage. The current situation of the building was investigated by using slightly destructive and non-destructive test methods. Flat-jack and shear tests were used in order to identify the mechanical properties of masonry walls according to the ASTM standards. The operational modal analysis test method was used in order to understand its dynamic characteristics. After the diagnosis phase, a finite element model was prepared and calibrated according to the in-situ test results. The reinforcement studies were performed according to the finite element modal analysis results. Finally, the differences between the dynamic properties of the structure were evaluated by vibration tests before and after the restoration works.